Dinamika Atmosfer pada Kejadian Banjir di Kota Kendari Maret 2024 - Ayudya Safitri; Rahmad Hidayat; Nitrawati Bahir; M. Tufaila Hemon (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2025)
Atmospheric dynamics analysis is important in the context of tropical flooding because changes in wind, temperature, and humidity influence the intensity and location of extreme rainfall events that trigger hydrometeorological disasters. The massive flooding in Kendari City in March 2024 was causing economic losses and disrupting community activities. The objective of this study is to analyze the meteorological factors influencing the flooding in Kendari City in March 2024, focusing on atmospheric dynamics, sea surface temperature, wind patterns, and Madden-Julian Oscillation (MJO) activity. The method used is a quantitative approach with descriptive analysis, based on rainfall data from three rain posts in Kendari City, Sea Surface Temperature data, Wind Direction and Speed ​​data at the 850 mb layer, and Outgoing Longwave Radiation data with a time period of March 2024. The results of the study indicate that the extreme rainfall that occurred on March 7, 2024 (170.6 mm) was triggered by a combination of three main factors, namely high sea surface temperatures (0.8oC - 1.8oC), wind convergence patterns in the Southeast Sulawesi region (the presence of wind eddies in the southern part of the Southeast Sulawesi region), and the activity of the MJO. This study can be a reference for local governments, communities, and academics in improving flood preparedness, mitigation, and management more effectively.